Design and analysis of high performance and low power matrix filling for DNA sequence alignment accelerator using ASIC design flow: article - Abd Razak, Nurul Farhana (2009)
Efficient sequence alignment is one of the most important and challenging activities in bioinformatics. Many algorithms have been proposed to perform and accelerate sequence alignment activities. Among them Smith-Waterman (SW) is the most sensitive (accurate) algorithm. This paper presents, novel approach and analysis of High Performance and Low Power Matrix Filling for DNA Sequence Alignment Accelerator by using ASIC design flow. The objective of this paper is to improve the performance of the DNA sequence alignment and to optimize power reduction of the existing technique by using Smitt Waterman (SW) algorithm. The scope of study is by using the matrix filling method which is in parallel implementation of the Smith-Waterman algorithm.